Angiotensin-(1-7) Modulates Angiotensin II-Induced Vasoconstriction in Human Mammary Artery - Luis Mendonca (2014)
The renin-angiotensin system plays a key role in cardiovascular pathophysiology and one of its members, angiotensin-(1-7) (ANG-(1-7)), is now recognized as a peptide with the ability to counter-regulate angiotensin II (ANGII) effects. We sought to investigate ANG-(1-7) actions in human vessels, particularly its effect on ANGII-induced vasoconstriction in human mammary arteries (HMA). Samples of HMA from patients submitted to coronary revascularization (22 patients, mean age 67 years) were cut into small rings, mounted in a myograph bath system, normalized and allowed to contract and dilate isometrically. In baseline experiments, the rings were incubated with ANG-(1-7) or vehicle, followed by increasing concentrations of ANGII. This protocol was repeated in the presence of A-779, PD123177, losartan and after mechanical endothelium removal. Western blot analysis and immunofluorescence were also performed in order to verify the presence of Mas receptor in HMA. ANG-(1-7) significantly attenuated ANGII-induced contraction, producing a maximal inhibition of approximately 65.2 %. This effect was not abolished by A-779, PD123177 or endothelium removal. In the presence of losartan, ANGII response was attenuated and no differences were observed between ANG-(1-7) and vehicle treated rings. Finally, we observed, for the first time, that the Mas receptor is expressed in HMA endothelium. ANG-(1-7) significantly attenuates ANGII-induced vasoconstriction and, although the Mas receptor is expressed in HMA, this effect seems to be independent of its activation. Additionally, AT(2) receptor and endothelium are not involved in this mechanism, which suggests a direct effect on smooth muscle cells.